Development and validation of a compact biodiesel surrogate fuel model for multi-dimensional cfd applications / Poon Hiew Mun - Poon, Hiew Mun (2019)
This work reports the development of a reduced biodiesel surrogate fuel model for multi-dimensional computational fluid dynamics (CFD) simulations. The model is derived using an integrated chemical kinetic mechanism reduction scheme and the final chemistry comprises 84 species with 264 elementary reactions. The model is first validated in zero-dimensional (0-D) chemical kinetic calculations under a wide range of auto-ignition and jet-stirred reactor (JSR) conditions. The ignition delays (ID) and species profiles computed by the reduced model are in well agreement with those of the detailed model. Apart from that, the experimental species profiles of rapeseed methyl ester (RME) oxidation in a JSR are also reasonably reproduced. Subsequently, the fidelity of the model is further assessed in two-dimensional (2-D) CFD simulations of a constant volume combustion chamber at two ambient temperatures of 900 K and 1000 K. The surrogate model is validated against the experimental results of soy-methyl ester (SME) combustion using the corresponding fuel compositions. Comparisons of the computations with the experimental measurements reveal that ID, lift-off lengths (LOL) and soot volume fractions are reasonably well replicated by the model. Following that, the applicability of the reduced model to serve as a universal surrogate model for other biodiesel feed-stocks, such as palm-methyl ester (PME) and sunflower-methyl ester (SFME), is investigated. The compositions of the reduced model are varied according to the saturation/unsaturation levels in each fuel. Each configuration is first validated in 0-D kinetic simulations, followed by the 2-D spray combustion simulations. The findings show that the calculated IDs and LOLs decrease with increasing unsaturation level. Soot formation is also enhanced with the presence of greater amount of unsaturated ester. In this work, it is demonstrated that the reduced model can potentially be used to predict the reactivity of biodiesel feed-stocks with low degree of saturation (≤ 30 %) in both kinetic and CFD spray simulations.